Proof of an extension of E. Sawyer’s conjecture about weighted mixed weak-type estimates - Kangwei, Li (2019)
We show that if v∈ A∞ and u∈ A1, then there is a constant c depending on the A1 constant of u and the A∞ constant of v such that ∥T(fv)v∥L1,∞(uv)≤c‖f‖L1(uv),where T can be the Hardy–Littlewood maximal function or any Calderón–Zygmund operator. This result was conjectured in Cruz-Uribe et al. (Int Math Res Not 30:1849–1871, 2005) and constitutes the most singular case of some extensions of several problems proposed by Sawyer and Muckenhoupt and Wheeden. We also improve and extends several quantitative estimates.